2020
DOI: 10.1111/petr.13827
|View full text |Cite
|
Sign up to set email alerts
|

Minding the gap—Providing quality transplant care for South African children with acute liver failure

Abstract: Pediatric ALF is rare but life-threatening and may require urgent transplantation. In low and middle-income countries, access to transplantation is limited, deceased organ donation rates are low, and data on outcomes scarce. The Wits Donald Gordon Medical Centre, in Johannesburg, is one of only two centers in South Africa that perform pediatric liver transplant. We describe the etiology, clinical presentation, and outcomes of children undergoing liver transplant for ALF at our center over the past 14 years. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 23 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Liver transplantation has interrupted the clinical trajectory of PALF [17,41]. In South Africa's heterogenous population, access to transplantation is limited and dependent on many factors like socio-economic status, geographical location, access to healthcare, transportation availability to health care facilities and many other factors [19]. In our cohort there were many patients who, although referred for transplantation, were too ill to be transplanted.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Liver transplantation has interrupted the clinical trajectory of PALF [17,41]. In South Africa's heterogenous population, access to transplantation is limited and dependent on many factors like socio-economic status, geographical location, access to healthcare, transportation availability to health care facilities and many other factors [19]. In our cohort there were many patients who, although referred for transplantation, were too ill to be transplanted.…”
Section: Discussionmentioning
confidence: 90%
“…This observational single centre study evaluated the prognostic indicators associated with poorer outcomes in pediatric patients with ALF in Gauteng, S.A, which is currently the location of the only pediatric transplant unit in S.A, performing both living related and ABO incompatible liver transplantation in PALF patients [19]. To our knowledge this is the only study on prognostic factors and scoring systems in PALF from Southern Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Our 13 Further to the high cost and morbidity/mortality, Bruckmann et al showed that HAV is currently the leading cause of paediatric acute liver failure requiring transplantation in South Africa, with even further expenses and disease burden to the health sector. 14 The study was limited by participant enrolment in a single urban centre. However, Kalafong Provincial Tertiary Hospital, services a wide community of informal settlement households with poor access to clean water and sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more www.nature.com/scientificreports/ than 1 in every 10 hepatitis A cases (13.3%) developed complicated hepatitis A or resulted in death 13 . Further to the high cost and morbidity/mortality, Bruckmann et al showed that HAV is currently the leading cause of pediatric acute liver failure requiring transplantation in South Africa, with even further expenses and disease burden to the health sector 14 .…”
Section: Discussionmentioning
confidence: 99%